Al-Maqam dan Al-Ahwal dalam Tasawuf - Rajab, Khairunnas (Jurnal Usuluddin, 2007)
Al-Maqamat and al-aḥwāl are two related parallel topics discussed in Sufism. Both are the effort of gaining the spiritual bounties through the process of tazkiyah al-nafs. There are many types of al-Maqamat and al-aḥwāl according to Sufis spiritual experiences such as tawbah, zuhd, ṣabr, tawakkal, riḍā, maḥabbah, khawf, tawaḍḍū`, taqwā, ikhlāṣ, shukr dan ma`rifah. The Sufis can only achieve these types of al-Maqamat and al-ahwal after their journey in takhalliyyah al-nafs, taḥalliyyah al-nafs and tajalliyyah al-nafs.